PENDIDIKAN KARAKTER DALAM CERITA ANAK BERJUDUL KECIL JADI KAWAN, BESAR JADI LAWAN KARYA TRI ISYANTI DAN SITI ANDARI - Siti Anafiah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
This study aims to describe the character education contained in a children’s story entitled Small So Comrade, Big So Opponent. The type of this research is descriptive qualitative. The object in this study is a children’s story entitled Small So Comrade, Big So Opponent written by Tri Isyanti and Siti Andari. The research data was collected through reading and taking notes techniques. The data analysis in this research is conducted by implementing pragmatic approach. The steps conducted are identifying, reviewing, interpreting, and describing the parts of the children’s story that can be utilized as the form of character education. The results of this research as it is depicted in the children’s story entitled Small So Comrade, Big So Opponent written by Tri Isyanti and Siti Andari portray that there is a character education value in terms of mitigating disaster. The children's storybook is set for 3rd grade of elementary school students who have environmental and social concerns towards flood disaster, just in case someday it strikes their place of being. There are five character educations depicted in the children's story which are environmental caring; social caring; generosity, being helpful and cooperative; respect and courtesy; and curiosity.